Facial proportions in different mandibular rotations in class I individuals - BAHROU , Shaghaf; HASAN , Abed Alkarim; KHALIL, Fadi (International Arab Journal of Dentistry (IAJD), 2014)
The aims of this study were to evaluate facial proportions in different types of mandibular rotation using various parameters, to explore gender dimorphism within each type and to evaluate the correlation between the mandibular rotation measurements and the facial proportions. Lateral cephalograms of a total of 62 class I subjects (30 males and 32 female), aged between 18-25 years, were studied. The sample was divided into forward, normal, and backward rotation subgroups. Nine soft tissue facial proportions and five skeletal proportions were measured on lateral cephalometric radiographs. The facial proportions data were analyzed using independent sample Student t-test and Pearson correlation analysis. The backward rotation subjects showed the lowest value for the proportion of total posterior facial height (TPFH) and total anterior facial height (TAFH) and proportion of lower posterior facial height (LPFH) and TPFH and the highest value for the proportion of Sn-Pn./Stms-Sn., while forward rotation subjects exhibited the lowest value for proportion of upper posterior facial height (UPFH) and TPFH. Gender dimorphism was recorded; males showed higher value for the proportion of TPFH and TAFH, as well as for the proportion of Sn-Me’/G-Me’ and Me’-Stmi/Me’-Sn in the backward rotation group. All the skeletal facial proportions were found correlated with mandibular rotation measurements (NS-GoMe, B, FH-GoMe, Bjork) while only the soft tissue proportion for G-Sn/Sn-Me’, Sn-Me’/G-Me’ and G-Sn/G-Me’ were correlated with mandibular rotation measurements. The soft tissue drape particularly facial vertical dimensions are influenced by the underlying skeletal vertical pattern.